Production of a peptide composition with antioxidant and ace inhibitory properties - Saari, Nazamid; Chay, Shyan Yea; Ebrahimpour, Afshin; Abdul Hamid, Azizah; Bakar, Jamilah; Syed Muhammad, Sharifah Khairidah (2013)
The present invention pertains to a process for manufacturing a proteolysate with antioxidant and ACE inhibitory properties, the isolate produced according the method of the invention, and peptides isolated therefrom. The products of the invention ar particularly useful for the treatment of cardiovascular diseases and thus can be used as medicines or as food additives or supplements.